Depending Radionuclide Iodine for Diagnosis and Treatment Thyroid Cancer (Eurasian Journal of Research, Development and Innovation, 2024)
The fastest rising cancer in women is Thyroid cancer . Current treatment including surgery (total thyroidectomy) followed by thyroid hormone therapy. Radioactive iodine therapy is used in patients with an intermediate or higher risk of persistent or recurrent thyroid cancer. Radioactive iodine works as a “magic bullet” by getting taken up by both normal and cancerous thyroid cells and destroying them. Similarly, radioactive iodine can be used to destroy thyroid cancer cells if the cancer returns